2018
DOI: 10.1093/ee/nvy074
|View full text |Cite
|
Sign up to set email alerts
|

Ovary Development and Cold Tolerance of the Invasive Pest Drosophila suzukii (Matsumura) in the Central Plains of Kansas, United States

Abstract: Environmental challenges presented by temperature variation can be overcome through phenotypic plasticity in small invasive ectotherms. We tested the effect of thermal exposure to 21, 18, and 11°C throughout the whole life cycle of individuals, thermal exposure of adults reared at 25°C to 15 and 11°C for a 21-d period, and long (14:10 hr) and short (10:14 hr) photoperiod on ovary size and development in Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) cultured from a recently established population in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 78 publications
2
22
0
Order By: Relevance
“…1). The basal cold survival of control flies measured after exposure to Ϫ5°C for 100 min was similar to data reported by Jakobs et al (45), and Everman et al (28), (i.e., 20% survival after 1 h at Ϫ7°C and 10% after 1 h at Ϫ6°C, respectively), and cold acclimation greatly promoted acute cold stress survival, as previously reported (105). Shorter CCRT after adult acclimation has also been reported by Jakobs et al (45).…”
Section: Cold Acclimation Increases Cold Tolerance Of D Suzukiisupporting
confidence: 89%
See 2 more Smart Citations
“…1). The basal cold survival of control flies measured after exposure to Ϫ5°C for 100 min was similar to data reported by Jakobs et al (45), and Everman et al (28), (i.e., 20% survival after 1 h at Ϫ7°C and 10% after 1 h at Ϫ6°C, respectively), and cold acclimation greatly promoted acute cold stress survival, as previously reported (105). Shorter CCRT after adult acclimation has also been reported by Jakobs et al (45).…”
Section: Cold Acclimation Increases Cold Tolerance Of D Suzukiisupporting
confidence: 89%
“…These winter flies probably resulted from larvae and pupae that developed in fruits in autumn (50). Hence, they may acclimate during both development and as adult (28,84,90,93,101,105). Therefore, it is likely that wild D. suzukii can use physiological adjustments similar to the ones we described here to enhance their cold tolerance and successfully overwinter in invaded areas.…”
Section: Perspectives and Significancementioning
confidence: 73%
See 1 more Smart Citation
“… Everman et al (2018) found a similar rapid cold-hardening response in non-acclimated flies exposed at 4°C for 2 h. This fly is also capable of acquiring cold tolerance via acclimation at adult stage ( Jakobs et al, 2015 ; Wallingford and Loeb, 2016 ), or via developmental acclimation ( Toxopeus et al, 2016 ; Wallingford and Loeb, 2016 ). In D. suzukii , developmental acclimation at temperatures below 12°C (combined or not with short photoperiod) results in a phenotype showing increased body size, dark pigmentation, reproductive arrest, and enhanced cold tolerance; this phenotype, referred to as “winter morph”, is supposed to be the overwintering form of D. suzukii ( Stephens et al, 2015 ; Shearer et al, 2016 ; Toxopeus et al, 2016 ; Wallingford and Loeb, 2016 ; Everman et al, 2018 ). Effect of the different forms of acclimation on subsequent cold tolerance has been rather well described in D. suzukii , but surprisingly, the mechanisms underlying cold tolerance acquisition through acclimation in this species are still poorly understood.…”
Section: Introductionmentioning
confidence: 67%
“…Low temperature tolerance changes with morphology as those with a dark morphology have a lower temp resistance than light morphs [75]. The dark morph is induced by low temperatures, independent of day length, and is accompanied by increased body size and reproductive quiescence, which likely collectively contribute to increased thermal stress resistance [7679].…”
Section: Discussionmentioning
confidence: 99%